(3MGTjI Ydi GdeUHGMs - (3fGUQ Hf YHO GdSjO CHj GdecGQe GHf Ydj, CHh GdaJM, HQgGf GdOjf GdNhGQRej GdeWQRj , J (B610 (3g`s ((3eOjfI GdefjG s)
(3ChdgG (B:s
(3bGd GdGeGe GdeWQRj cdeI ajgG eYfi GdTQW, abhdc cGfJ GdaGA dGReI dgG s
(3BNQgG (B:s
(3agPG HGH GdEWfGH dcfg jaVj Edi GdedGc aGbJUQJ Ydi gPG GdbOQ s
(3GdfSNI HgG MhGTs
(3fSNI HgG WeSs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B71s
Keywords: (3GdfMhs